2020
DOI: 10.1093/femsec/fiaa006
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistome and microbial community structure during anaerobic co-digestion of food waste, paper and cardboard

Abstract: Solid organic waste is a significant source of antibiotic resistance genes (ARGs) and effective treatment strategies are urgently required to limit the spread of antimicrobial resistance. Here, we studied ARG diversity and abundance as well as the relationship between antibiotic resistome and microbial community structure within a lab-scale solid-state anaerobic digester treating a mixture of food waste, paper and cardboard. A total of 10 samples from digester feed and digestion products were collected for mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…A high-throughput qPCR (HT-qPCR) was used to quantify the ARGs and MGEs in soil samples. The array included 384 primers targeting ARGs (319) and MGEs (57); additionally, the taxonomic marker genes were included in the array ( Stedtfeld et al, 2018 ; Kanger et al, 2020 ; Pu et al, 2020 ). All reactions were performed in the Takara SmartChip real-time PCR system, as described previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-throughput qPCR (HT-qPCR) was used to quantify the ARGs and MGEs in soil samples. The array included 384 primers targeting ARGs (319) and MGEs (57); additionally, the taxonomic marker genes were included in the array ( Stedtfeld et al, 2018 ; Kanger et al, 2020 ; Pu et al, 2020 ). All reactions were performed in the Takara SmartChip real-time PCR system, as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…All reactions were performed in the Takara SmartChip real-time PCR system, as described previously. Three technical replicates were performed for each sample, and a non-template negative control was included in each HT-qPCR run ( Kanger et al, 2020 ). A threshold cycle (Ct) of 31 was used as the detection limit, and only all three replicates with Ct lower than 31 were regarded as genes detected in that sample.…”
Section: Methodsmentioning
confidence: 99%
“…ethanol and 5 M NaCl prior to sequencing (Kanger et al, 2020). The final DNA concentration was measured by Nanodrop (NanoDrop1000 Spectrophotometer, Thermo Fisher Scientific).…”
Section: Dna Extraction and Quantitative Polymerase Chain Reaction (Q...mentioning
confidence: 99%
“…We found that the α-diversity of ARGs were significantly higher in the HTR than in the NCR; the β-diversity in the HTR and MPR was also significantly different from that in the NCR (Figure 4). The most important sources of pollution in the HTR are also important reservoirs of ARGs, such as food waste, plastic bottles, and carton packaging (Yang et al, 2019;Kanger et al, 2020). High-protein foods, such as meat, can increase the diversity of ARGs during the decomposition process, thereby increasing the risk of their transmission and diffusion in the environment .…”
Section: Figurementioning
confidence: 99%